Hydrothermal synthesis and characterization of Dy-doped MoO3 nanobelts for using as a visible-light-driven photocatalyst - Anukorn Phuruangrat (2018)
© 2017 Elsevier B.V. Dy-doped MoO3 nanobelts were synthesized by hydrothermal method. The phase, morphology and vibration modes of the samples were analyzed by X-ray diffraction, transmission electron microscopy, Fourier transform infrared spectrometry and Raman spectroscopy. In this research, MoO3 and Dy-doped MoO3 were specified as orthorhombic MoO3 nanobelts with their growth along the [0 0 1] direction. Photocatalytic activity of Dy-doped MoO3 nanobelts was investigated by photodegradation of methylene blue (MB) under visible radiation. It was found that 77.34% of MB was degraded in the solution containing pure MoO3 nanobelts, while 97.76% of MB was obviously degraded in the solution containing 3 mol% Dy-doped MoO3.